The graphic design process : how to be successful in design school - Nottingham, Anitra; Stout, Jeremy (London ; New York, NY : Bloomsbury Visual Arts, 2019)
"One of the main challenges students face upon entering design school is little knowledge of the field, its terminology and best practices. Unsurprisingly, most new students have never fully developed a concept or visual idea, been in a critique, or have been asked to explain their work to others. This book demystifies what design school is really like and explains what will be experienced at each stage, with particular focus on practical advice on topics like responding to design briefs and developing ideas, building up confidence and understanding what is expected. Student work is critiqued to show how projects are really assessed. Profiles highlight how professional designers themselves address client briefs. Tips for real-life problems are outlined, like getting stuck and dealing with critical feedback. Written by experienced instructors, this is the perfect guide for those starting their design education"--
Design thinking -- The 4D design process -- How this book is structured -- Discover -- Design -- Develop -- Deploy.
Includes bibliographical references and index.
Keywords: Commercial art -- Study and teaching; Graphic arts -- Study and teaching